DIGITAL POLITICAL THOUGHT AND THE REWRITABLE USER - Troumbley, Rex (AoIR Selected Papers of Internet Research, 2015)
Much of the existing political research on digital technologies focuses on the ontological and ethical implications of their use, but those studying political thought have yet to adequately account for how “thought” is as much about how technologies think as it is what they think about. Additionally, new techniques for directing digital discourse and behavior, which Thaler and Sunstein describe in their recent book_Nudge_as “relatively weak, soft, and nonintrusive,” are shaping users as they use and think through digital technologies. Without a better understanding of these new forms of governance, we are left with an inadequate analysis of digital politics and outmoded conceptions of power. This paper considers how the translation of text, sound, image, and video into a universal medium of 1s and 0s deforms contemporary political theory, and what can be thought through digital technologies, in ways which exceed traditional understandings of censorship. In order to understand how digital systems attempt to manage discourse and behavior which is uncontrollable, the project examines the psychiatric treatment of uncontrollable cursing (Tourette syndrome) and the unpredictable or emergent behavior of non-human agents influencing the sorting operations of Google’s Search algorithm. The paper ends by considering several proposed interventions into the way users do political thinking through devices, at the level of pre-speech and pre-diction, and suggests that leveraging the “distributed agency” of algorithms might be one way to evade what Gilles Deleuze identified as the “control society” enabled by contemporary digital technologies.